The Application of Cooperative Learning (Talking Stick) with Multimedia to Improve Javanese Reading Skills to Fifth Grade Students of SD Negeri 1 Panjer in Academic Year of 2022/2023 - Andini, Mila Esa; Susiani, Tri Saptuti; Ngatman, Ngatman (Universitas Sebelas Maret, 2023)
The study aimed to improve Javanese script reading skills to fifth grade of SD Negeri 1 Panjer in academic year of 2022/2023 through the application of Talking Stick with multimedia. It was a collaborative Classroom Action Research conducted in three cycles. The subjects were teachers and students of fifth grade at SD Negeri 1 Panjer in academic year of 2022/2023. The data were qualitative and quantitative. Data collection techniques were observation, interviews, and tests. Data validity used triangulation of sources and triangulation of sources techniques. Data analysis included data reduction, data presentation, and drawing conclusions. The percentages of students’ passing grades in Javanese script reading skills were 72% in the first cycle, 80% in the second cycle, 92% in the third cycle. It concludes that the application of Talking Stick with multimedia improves Javanese script reading skills to fifth grade students of SD Negeri 1 Panjer in academic year of 2022/2023.